Unmet need for chronic mental ill health: A population-based record linkage study - Rosato, Michael; Tseliou, Foteini; O'Reilly, Dermot (International Journal of Population Data Science, 2019)
Introduction It is widely recognised that many people with chronic mental ill health do not receive the treatment they need, with socio-demographic and socio-economic factors contributing to mental healthcare access and receipt of treatment. However, recently different perceptions have emerged following reports of over-treatment or over-medication of a proportion of the population presenting to primary care settings with poor mental health. Objectives This study aimed to investigate which factors are associated with the presence of poor mental health and the likelihood of being in receipt of pharmacological treatment for those who report chronic mental ill health. Methods The methodology was a record linkage of the 2011 Northern Ireland Census returns and a population-wide database of prescribed medications. The presence of a chronic mental health condition, as assessed through a self-reported question in the 2011 Census, was compared to electronic administrative records on psychotropic medication use in the twelve months following the Census. Results This study shows that those of non-white background (OR 0.38 95%CI 0.26-0.54), who were never married (OR 0.67 95%CI 061-0.73), unemployed (OR 0.65 95%CI 0.53-0.81) or living in a rural area (OR 0.88 95%CI 0.79-0.98) were less likely than their peers to receive medication for their poor mental health. Conclusions Some but not all of the observed variations may represent unmet need, but further studies are required to understand the knowledge of and attitudes towards healthcare services of groups (such as ethnic minorities and unemployed) who are identified as being less likely to receive treatment. Highlights Self-reported chronic mental ill health varied by socio-demographic and socio-economic characteristics. Although a high proportion of people received psychotropic medication for their mental ill health, there were evident social patterns among those who do not receive treatment. Ethnic minorities, those whose were not married or unemployed were considerably more likely to experience unmet need.